2014
DOI: 10.1101/gr.167668.113
|View full text |Cite
|
Sign up to set email alerts
|

General approach for in vivo recovery of cell type-specific effector gene sets

Abstract: Differentially expressed, cell type-specific effector gene sets hold the key to multiple important problems in biology, from theoretical aspects of developmental gene regulatory networks (GRNs) to various practical applications. Although individual cell types of interest have been recovered by various methods and analyzed, systematic recovery of multiple cell type-specific gene sets from whole developing organisms has remained problematic. Here we describe a general methodology using the sea urchin embryo, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 32 publications
(33 reference statements)
1
37
0
Order By: Relevance
“…S3 (see legend for identities of these transcripts). The result is clear; exactly as in the preceding study on transcripts enriched in skeletogenic cells (Barsi et al, 2014), transcript sets isolated by this method are, by direct observation, specifically expressed in the expected spatial domains. FACS isolation of the cells expressing the respective regulatory genes thus effectively worked to separate out these embryonic cell populations, irrespective of the very distinct cell types and embryonic locations sampled.…”
Section: Genes Enriched In the Transcriptomes Of Each Cell Populationsupporting
confidence: 81%
See 3 more Smart Citations
“…S3 (see legend for identities of these transcripts). The result is clear; exactly as in the preceding study on transcripts enriched in skeletogenic cells (Barsi et al, 2014), transcript sets isolated by this method are, by direct observation, specifically expressed in the expected spatial domains. FACS isolation of the cells expressing the respective regulatory genes thus effectively worked to separate out these embryonic cell populations, irrespective of the very distinct cell types and embryonic locations sampled.…”
Section: Genes Enriched In the Transcriptomes Of Each Cell Populationsupporting
confidence: 81%
“…This was done in extenso in the preceding study on skeletogenic cells (Barsi et al, 2014). In that study, virtually every one of a large number of genes indicated by transcriptome analysis of the presumed skeletogenic population to be specifically expressed was indeed shown by in situ hybridization to be transcribed in skeletogenic cells.…”
Section: Genes Enriched In the Transcriptomes Of Each Cell Populationmentioning
confidence: 91%
See 2 more Smart Citations
“…New quantitative transcriptome methods have enabled us to define the set of all factors relevant to a given network (Barsi et al, 2014;Barsi, Tu, et al, 2015;Fischer et al, 2014;Tulin et al, 2013). However, once the players are known, researchers must navigate a low-throughput bottleneck when searching for active modules regulating network genes.…”
Section: And Exon 2 (Thick Black Bars) the Intronic Cis-regulatory Rmentioning
confidence: 99%